Abandono paterno, efectos en el consumo adictivo de cocaína en un joven de 17 años - Reyes Nivela, Nashaly Farley (2019)
The present study is descriptive qualitative, what was sought was the approach and interpretation of the reality that perceived and affected a 17-year-old with the absence of the father figure being the main trigger for the start of consumption and subsequent fall in addiction, therefore we sought to find the moment since the consumption began and when it was in absolute necessity to continue consuming this brought about the deterioration and drastic change of the young man, changing his friendships, his character changed completely, of a Young docile a young man totally aggressive, insecure, problematic, sometimes even stealing to get means to encourage his vices. The objective of this research Identify the effects of parental absence that affect the use of psychoactive substances (SPA) in a 17-year-old boy. It is necessary to highlight the importance of individual psychological support in rehabilitation centers contributing to the comprehensive rehabilitation of patients who are in recovery treatment to stop consuming. Finally, it can be said that the psychologist has not joined an intervention already formed, but that with his work he has contributed to the development of the same, being in turn forced to give increasingly specialized answers as more complex demands have been He has had in his intervention